Perioperative cytokine profile during lung surgery predicts patients at risk for postoperative complications-A prospective, clinical study. - Kai B Kaufmann; Sebastian Heinrich; Hans Felix Staehle; Lioudmila Bogatyreva; Hartmut Buerkle; Ulrich Goebel (PLoS ONE)
Background Postoperative complications after lung surgery are frequent, having a detrimental effect on patients' further course. Complications may lead to an increased length of hospital stay and cause additional costs. Several risk factors have been identified but it is still difficult to predict contemporary which patients are at risk. We hypothesized that patients who show an increased inflammatory response at the time of wound closure and 24 hours after surgery are at risk of postoperative complications within 30 days after surgery. Methods Postoperative complications (pulmonary, cardiac, neurological and renal) of 96 patients scheduled for lung surgery at the Medical Center-University of Freiburg were analyzed in this prospective, clinical study. Blood samples for cytokine analysis (Interleukin (IL)-6, IL-8, IL-10, Tumor necrosis factor [TNF]-α, IL-1ß and IL12p70) were taken before surgery, at wound closure and 24 hours after surgery. Cytokine levels of patients with and without postoperative complications were analyzed by Receiver operating characteristic (ROC) curve analysis. To adjust the results according to existing covariates a multivariate logistic regression analysis was conducted. Results The complication and non-complication group differed significantly according to nicotine dependency, Angiotensin-receptor-II blocker medication, rate of thoracotomy and preoperative lung function. The intraoperative hemodynamic parameters and therapy did not differ between the groups. Twenty-nine patients (30%) developed postoperative complications within 30 days after surgery. Plasma concentrations of IL-6, IL-10 and IL-8 at the time of wound closure and 24 hours after surgery were higher in the complication group. Multivariate regression analysis on postoperative complications revealed an Odds ratio of 56 for patients with IL-6 and IL-8 levels above the 3rd quartile measured on the first postoperative day. Conclusions Perioperative detection of increased plasma concentrations of inflammatory cytokines in lung surgery may be used in addition to other clinical predictors to identify patients at risk for postoperative complications. Trial registration German Clinical Trials Register 00006961.